Analisis Pengaruh Lingkungan dan Beban Kerja Terhadap Komitmen Organisasi di Rsud Kabupaten Padang Pariaman - Devide Bettawinda (Journal of Business and Economics (JBE) UPI YPTK, 2022)
This study aims to determine how much influence the work environment has on the organizational commitment of the Padang Pariaman District Hospital with work as an intervening variable. The research variables are work environment (X1), workload (X2) work goals (Z), and organizational commitment (Y). Methods of collecting data through surveys and distributing questionnaires with a sample of 73 respondents. The analytical methods used are validity and reliability tests, path analysis, and multiple regression analysis, for hypothesis testing used a t-test and F test. The results show a) That partially there is a positive and insignificant effect of work environment on job satisfaction. b) That partially there is a negative and significant effect of workload on job satisfaction. c) That partially there is a positive and significant influence on the work environment on organizational commitment. d) That partially there is a positive and significant influence on the workload of organizational commitment. e) That partially there is a positive and significant effect of job satisfaction on organizational commitment. f) goals do not mediate the work environment on organizational commitment. g) work goals do not mediate workload on organizational commitment. Figures Based on the Adjust R square equation 1 obtained by 0.467 or 46.7%, this shows that the proportion of the contribution of Model I independent variables Work environment (X1) and workload (X2) to the activity-dependent variable (Z) is 46.7%, while the remaining 53.3% is influenced by other variables that do not have to be studied